The Interest of Technology Adoption in E-Commerce Mobile Apps Using Modified Unified Theory of Acceptance and Use of Technology 2 in Indonesia - Dini Turipanam Alamanda; Lili Adi Wibowo; Soviyan Munawar; Adinda Khoeru Nisa (AIBPM Publisher, 2021)
The development of e-commerce in Indonesia rapidly grows along with the consumer preference for online shopping. This study aims to analyze people’s interest in adopting popular e-commerce mobile apps in Indonesia with the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) approach. Of the many e-commerce in Indonesia, only five popular e-commerce are the focus of this study. The quantitative method with the verification type was adopted. A survey was conducted and questionnaires were distributed online toward 400 respondents who are users of popular e-commerce in Indonesia. The collected data was analyzed using Partial Least Square (PLS). The findings show that performance expectations and promotion conditions have a significant effect on behavioral intentions, and habits and behavioral intentions have a significant effect on use behavior. The moderator variable of age has a significant effect on the relationship between habit and use behavior, while price value, hedonic motivation, and habit on behavioral intention are moderated by the age variable. Gender variable as the second moderator did not have a significant effect on all relationships. The results can be used by e-commerce as an evaluation and map out future marketing strategies.